The Implementation Of Steller Application In Learning Writing Descriptive Text - Jauhar Helmie; Vina Nurviyani; Dewi Susilawati (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
This study aims to investigate of implementation of Steller application to improve students’ writing Descriptive text and students’ responses about Steller application in writing Descriptive text. This study employed Classroom Action Research (CAR) method proposed by Kemmis and McTaggart (1998, cited in Burns, 2009). This research consisted of two cycles and each cycle consisted of four steps, they were: planning, actin, observation, and reflection. Each cycle was conducted in two meetings. To collect and analyze the data, the researcher used observation, questionnaire, and test. The result of this research shows that using Steller application in learning writing Descriptive text can improve students’ writing Descriptive text. The improvement of students’ writing Descriptive text also supported by the achievement of students’ test score. The students’ mean score of pre cycle test was 63.32, the mean score of test in cycle 1 was 73.58 and the mean score of test in cycle 2 was 79.19. it means that score test of cycle 1 was higher than pre cycle test and score test of cycle 2 was higher than mean score of test in cycle 1. The students’ responses showed that they were interested in learning writing Descriptive txt, because it was easier for them to write, it increased their motivation in learning, and Steller application game the students easy steps to write Descriptive text. Therefore it can be concluded that the implantation of Steller application improves students’ writing Descriptive text significantly at tenth grade of SMA Pasundan Cikalongkulon Cianjur.